Evaluation of buccolingual and linguobuccal implants in the atrophic posterior mandible: A finite element analysis study - Moyfat Karimov; Goksel Timarcioglu; Celal Candirli (Journal of Oral Biology and Craniofacial Research)
Aim: This study aims to evaluate the stress distribution on buccolingual and linguobuccal tilted implants in the atrophic posterior mandible using finite element analysis. Material and methods: Twelve digital models of implants with varying lengths (8.5 mm, 10 mm, 11.5 mm) and angles (20°, 25°) were created. These implants were analyzed under 150 N vertical and oblique forces to assess stress distribution on both implants and surrounding bone. Results: Linguobuccal implants generally exhibited lower maximum principal stress in cortical bone, while buccolingual implants showed lower minimum principal stress. Longer implants reduced stress under oblique loading. Conclusion: Tilted implants, particularly using the linguobuccal method, are effective for stress distribution in the atrophic posterior mandible. Further research should explore varying implant diameters and multiple placements for optimization.